2014
DOI: 10.1039/c4cp00832d
|View full text |Cite
|
Sign up to set email alerts
|

Non-equilibrium segmental dynamics driven by multiwall carbon nanotubes in PS/PVME blends

Abstract: The present paper discusses the effect of multiwall carbon nanotubes (MWNTs) on the structural relaxation and the intermolecular cooperativity in dynamically asymmetric blends of PS/PVME (polystyrene/poly(vinyl methyl ether)). The temperature regime where chain connectivity effects dominate the thermodynamic concentration fluctuation (T/Tg > 0.75, Tg is the glass transition temperature of the blends) was studied using dielectric spectroscopy (DS). Interestingly, in the blends with MWNTs a bimodal distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…77 Bimodal relaxations suggesting different 'dynamical' environments were noted in the case of PS/PVME blends in the presence of MWNTs. 80 The dielectric loss modulus spectra showed a bimodal distribution in the presence of MWNTs. This is the characteristic of a heterogeneous environment.…”
Section: Polymer Grafted Nanoparticlesmentioning
confidence: 96%
“…77 Bimodal relaxations suggesting different 'dynamical' environments were noted in the case of PS/PVME blends in the presence of MWNTs. 80 The dielectric loss modulus spectra showed a bimodal distribution in the presence of MWNTs. This is the characteristic of a heterogeneous environment.…”
Section: Polymer Grafted Nanoparticlesmentioning
confidence: 96%
“…It can be found that when the temperature is in the range where the segmental dynamics is active in the frequency window, the temperature‐dependent loss peaks corresponding to segmental dynamics ( α relaxation) of PVME can be superposed for unfilled, filled systems and the width and maximum of hardly change with the incorporation of A200 or R974, indicating that the nanoparticles can hardly retard the segmental dynamics of PVME in the homopolymer or miscible blend matrix. In some previous works, the restriction of segmental mobility is induced by surface adsorption of polymer to nanoparticles and then leads to the retarded kinetics of phase separation, while the influence of nanoparticles on the segmental dynamics is clearly not the main cause for the constrain phase separation in our study. Similar phenomenon with the unaltered glass transition temperature ( T g ) or segmental relaxation time ( τ seg ) were also observed for other nanocomposties …”
Section: Resultsmentioning
confidence: 46%
“…13,29,30 In the case of PS/PVME blends, the segmental relaxations can be coupled with the conductivity. Apart from increasing the local concentration in a given phase, it also manipulates the phase separation dynamics.…”
Section: Evolution Of Electrical Conductivity Using Electro-rheology mentioning
confidence: 99%